2013
DOI: 10.1051/0004-6361/201322127
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of spin to jet-disk coupling in black holes

Abstract: Context. The spin of supermassive black holes could power jets from active galactic nuclei (AGN), although direct observational evidence for this conjecture is sparse. The accretion disk luminosity and jet power, on the other hand, have long been observed to follow a linear correlation. Aims. If jet power is coupled to black hole spin, deviations from the jet-disk correlation for a sample of AGN can be used to probe the dispersion of the spin parameter (a) within this sample. Methods. To obtain a large sample … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Only 2 quasars have η jet ≥ 1. This low jet production efficiency is consistent with the study by van Velzen & Falcke (2013) in which they used a correlation between optical and radio luminosities of 763 FR-II quasars utilizing the SDSS-FIRST catalog. This low efficiency is not significantly enhanced even if we set = 0.3 ( Figure 5).…”
Section: +26supporting
confidence: 89%
“…Only 2 quasars have η jet ≥ 1. This low jet production efficiency is consistent with the study by van Velzen & Falcke (2013) in which they used a correlation between optical and radio luminosities of 763 FR-II quasars utilizing the SDSS-FIRST catalog. This low efficiency is not significantly enhanced even if we set = 0.3 ( Figure 5).…”
Section: +26supporting
confidence: 89%
“…The jet powers in FR II quasars calculated using radio-lobe calorimetry [24] are a factor ∼50 smaller than jet powers calculated using spectral fits of γ-ray detected FSRQs when assuming n p = n e jet plasma [2] (see Figure 1). Measurements of radio luminosities of extended radio-structures in some FSRQs [27,28] has enabled a comparison of the results of the two jet power measurement techniques by applying both techniques to the same objects.…”
Section: Discussionmentioning
confidence: 82%
“…Problems with launching such powerful jets by standard accretion discs stimulated studies on the socalled magnetically arrested discs (MAD; Narayan et al 2003). In scenarios involving the MAD, the jet is powered by a fast spinning black hole (BH) immersed in a strong magnetic field supported by the ram pressure of the accretion flow (Tchekhovskoy et al 2011;McKinney et al 2012). As it has been theoretically estimated and numerically confirmed, the spin-extraction/MAD scenario allows launching jets with the power up to 3Ṁc 2 or so.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the spin-extraction/MAD model to radio loud quasars was questioned by van Velzen & Falcke (2013), who, by using energetics of radio lobes, found that the median value of the jet production efficiency, η j ≡ P j /Ṁc 2 , in a radio-selected sample of quasars with double radio sources is ∼0.01. If η j depended only on the BH spin, this would imply its average value much lower than those predicted by BH cosmological evolution (Volonteri et al 2013).…”
Section: Introductionmentioning
confidence: 99%